Radiostereometric migration analysis of the Cerafit femoral stem: 28 patients followed for 2 years - Tschunko, Franz; Wagner, Benedikt; Hong, Yutong; Söder, Stephan; Wölfel, Rainer; Müller, Lutz Arne; Forst, Raimund; Sesselmann, Stefan (Biomedizinische Technik, 2015)
Radiostereometric analysis (RSA) is the gold standard evaluating micromovements after total hip arthroplasty. The aim of this study was to investigate the migratory pattern of an uncemented femoral stem during the first 2 years after surgery. We followed 28 patients with a mean age of 57 (SD 13) years for the first two postoperative years. Radiostereometric analysis was used to measure the translation and rotation of the femoral component. The Harris hip score (HHS) was determined to evaluate the clinical outcome. No stem had to be revised. The mean HHS advanced from 35 (SD 11) preoperative to 89 (SD 10) 1 year after surgery. At the end of the observation period, mean subsidence of the stem was 0.26 mm (SD 0.82). Maximum total point motion (MTPM) was 1.23 mm (SD 1.22). The main distal migration took place up to 6 weeks after surgery with nearly no further subsidence up to 2 years postoperatively. All the measured migrations of the hip stem were very small. Results of the HHS demonstrate good clinical outcome. Long-term RSA is necessary to assess possible late migration of the Cerafit standard femoral stem.
EVALuna2:10856